ROHHAD syndrome without rapid-onset obesity: A diagnosis challenge - Desse, Blandine; Tran, Antoine; Butori, Mathilde; Marchal, Sarah; Afanetti, Michael; Barthélemy, Sébastien; Bérard, Etienne; Baechler, Elisabeth; Debelleix, Stéphane; Lampin, Marie-Emilie; Macey, Julie; Massenavette, Bruno; et al. (Frontiers in Pediatrics, 2022)
Background ROHHAD syndrome (Rapid-onset Obesity with Hypothalamic dysfunction, Hypoventilation and Autonomic Dysregulation) is rare. Rapid-onset morbid obesity is usually the first recognizable sign of this syndrome, however a subset of patients develop ROHHAD syndrome without obesity. The prevalence of this entity is currently unknown. Alteration of respiratory control as well as dysautonomic disorders often have a fatal outcome, thus early recognition of this syndrome is essential. Material and methods A retrospective, observational, multicenter study including all cases of ROHHAD without rapid-onset obesity diagnosed in France from 2000 to 2020. Results Four patients were identified. Median age at diagnosis was 8 years 10 months. Median body mass index was 17.4 kg/m². Signs of autonomic dysfunction presented first, followed by hypothalamic disorders. All four patients had sleep apnea syndrome. Hypoventilation led to the diagnosis. Three of the four children received ventilatory support, all four received hormone replacement therapy, and two received psychotropic treatment. One child in our cohort died at 2 years 10 months old. For the three surviving patients, median duration of follow-up was 7.4 years. Conclusion ROHHAD syndrome without rapid-onset obesity is a particular entity, appearing later than ROHHAD with obesity. This entity should be considered in the presence of dysautonomia disorders without brain damage. Likewise, the occurrence of a hypothalamic syndrome with no identified etiology requires a sleep study to search for apnea and hypoventilation. The identification of ROHHAD syndrome without rapid-onset obesity is a clinical challenge, with major implications for patient prognosis.